Komposisi Jenis Lamun (Seagrass) Di Kawasan Pantai Malagoso Desa Dumolodo Kecamatan Gentuma Raya Kabupaten Gorontalo - Nurul Auliyah (Universitas Gorontalo, 2018)
This research aims to identificated the composition of the type and seagrass beds density in malagoso beach, Dulomodo Village. The data was undetaken by survei method and transect square method. There are 3 stations where every stations will cut in 3 times. The analysis used and covering identification of the type of seagrass beds, density, coverage of seagrass and the closure of the parameters of the enviroment. The results of identification to research is found 4 types species of seagrass, there is Â Enhalus acoroides, Cymodocea serurulata, Halophila ovalis, Syringodium isoetifolium. Seagrass beds density ranged from 20 tegakan/m -600 tegakan/m. The parameter of water quality there are temperature 200C, salinity31 ppt, pH 8,2, brightess about 0,2-1 meters, the substrates are muddy and rocky.Keywords : Seagrass density, The seagrass bed, Malagoso beach.Â